Interleukin-23 drives innate and T cell-mediated intestinal inflammation. - Hue, S; Ahern, P; Buonocore, S; Kullberg, M; Cua, D; McKenzie, B; Powrie, F; Maloy, K (2006)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gastrointestinal tract involving aberrant activation of innate and adaptive immune responses. We have used two complementary models of IBD to examine the roles of interleukin (IL)-12 family cytokines in bacterially induced intestinal inflammation. Our results clearly show that IL-23, but not IL-12, is essential for the induction of chronic intestinal inflammation mediated by innate or adaptive immune mechanisms. Depletion of IL-23 was associated with decreased proinflammatory responses in the intestine but had little impact on systemic T cell inflammatory responses. These results newly identify IL-23 as a driver of innate immune pathology in the intestine and suggest that selective targeting of IL-23 represents an attractive therapeutic approach in human IBD.